Characterization of contemporary Anaplasma marginale strains for assessing antimicrobial-based anaplasmosis control strategies - Skinner, Brandt Charles (Kansas State University, 2020)
Bovine anaplasmosis is a tick-borne bacterial disease caused by Anaplasma marginale, a global pathogen estimated to cost the U.S. cattle industry >$300 million per year. Anaplasmosis treatment and control strategies rely heavily on tetracycline antibiotics; however, variations in susceptibility to this antibiotic class among A. marginale strains have been documented. Use of characterized contemporary strains is important when evaluating or re-evaluating antimicrobial management strategies. The first objective of our work was to locate and propagate two isolates of A. marginale actively circulating in Kansas cattle herds and characterize the progression of infection and clinical disease associated with these contemporary isolates in adult beef cattle. Adult beef cows naturally infected with contemporary A. marginale strains not previously isolated or studied were identified from the Kansas State University Cow-Calf herd, a herd naturally endemic for anaplasmosis. Blood samples containing these uncharacterized A. marginale isolates (KS1 and KS2) were collected and sub-inoculated into splenectomized calves for isolate propagation. To characterize the virulence and infection kinetics of these isolates, adult beef cows were inoculated with stabilates of A. marginale isolates ‘KS1’ and ‘KS2’, and clinical disease and isolate infection kinetics were monitored using packed cell volume and polymerase chain reaction assays, respectively. Animals challenged with KS1 reached clinical anaplasmosis by 35 days post-inoculation (dpi), approximately 3 days earlier than KS2-challenged animals. Animals challenged with KS1 reached a peak bacteremia of 3.43×10⁶ bacteria/mL blood, whereas KS2-challenged animals reached 9.46×10⁸ bacteria/mL blood. Both isolates caused clinical anaplasmosis in challenged animals that required treatment intervention; however, KS1 and KS2 had distinct infection kinetic characteristics. These isolates will be used in future studies to evaluate or re-evaluate the efficacy of antimicrobial-based anaplasmosis treatment and control strategies. Collectively, the work presented in this thesis will contribute to the need for data-driven recommendations for effective and judicious antimicrobial-based anaplasmosis management strategies.
Keywords: Anaplasma marginale; anaplasmosis; antimicrobial; genetic diversity